Shear wave velocity measurements of the brachial artery in a population with end-stage renal disease. (21st August 2018) - MacDonald, C; Ross, R; Houston, JG
Abstract: Introduction: Arterial elasticity measurements have been suggested as a possible biomarker for arterio-venous fistula failure. Elasticity can be non-invasively measured through ultrasonic induction of a shear-wave in tissue. The velocity of this wave is proportional to the square root of Young's Modulus. This pilot study sought to assess an imaging protocol to measure elasticity in the brachial artery via shear wave elastography (SWE) and determine if differences in shear wave velocity could be observed between a healthy group, and a group with end-stage renal disease (ESRD). Methods: 40 healthy volunteers were recruited into this study. All participants underwent US assessment of brachial artery elasticity via SWE. Brachial artery SWE images of 47 patients with ESRD were retrospectively analysed for comparison. Results: Brachial artery shear wave velocity was measured from each image. The imaging protocol was possible in all volunteers. The mean shear wave velocity was significantly lower in the patient group (3.2 ± 0.5 m/s in patients; 3.4 ± 0.4 m/s in volunteers, P < 0.05). Conclusion: The results from this pilot study suggest SWE measurements of brachial artery mechanics are feasible and can quantify arterial alterations possibly associated with ESRD. SWE may find use in the pre-operative assessment for patients awaiting arterio-venous fistula creation.